Rekonstruksi Sistem Pendidikan Islam Masa Dinasti Abbasiyah dalam Perspektif Pendidikan Kontemporer - Rika Purnamasari; Purnomo Purnomo; Muhamad Sidik Afandi (Prodi Pendidikan Agama Islam IAINU Kebumen, 2025)
This research seeks to examine the Islamic education system during the Abbasid Dynasty and explore the applicability of its values to modern Islamic education. Utilizing a qualitative approach with a historical-critical perspective, the study relies on library research, examining secondary sources such as books on Islamic civilization, academic articles, and contemporary studies on Islamic education. The analysis was carried out descriptively and critically through processes of data reduction, thematic organization, and contextual interpretation. Results reveal that Abbasid education was marked by the integration of religious and rational knowledge, supported by strong educational institutions, a rich culture of literacy and scholarship, ethically grounded academic freedom, and a focus on moral and spiritual development. These values remain relevant in addressing present-day challenges in Islamic education, such as the divide between fields of knowledge, limited research culture, and issues of character development. The study offers a framework for reconstructing Abbasid educational principles that is integrative, context-sensitive, and practically applicable to contemporary educational settings.